E-Commerce-Based Smes Taxpayer Compliance At Kpp Pratama Bandung Tegallega In 2022 - Sheilamanda Raihanty; Ardan Gani Asalam (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Taxes are defined as the most important revenue for the government in Indonesia, which is obtained through taxpayer contributions. However, the tax revenue is not optimal caused of the low interest of taxpayers and the lack of awareness, understanding, and socialization of the latest regulations by taxpayers, resulting in a low level of taxpayer compliance. This research aims to know the effect of Taxpayer Understanding, Tax Socialization, E-Filing, and E-Billing in Increasing Taxes on E-Commerce-Based SMEs Taxpayer Compliance. This research uses quantitative techniques with primary data obtained from questionnaires. The population taken is E-Commerce-based SMEs taxpayers registered at KPP Pratama Bandung Tegallega in 2022 using purposive sampling, and the sample used is 100. The results of this study state that Taxpayer Understanding, Tax Socialization, E-Filing, and E-Billing simultaneously affect E-Commerce Compliance among SMEs Taxpayers. Partially, the variables of Taxpayer Understanding, Tax Socialization, E-Filing, and E-Billing positively affect E-Commerce SMEs Taxpayer Compliance.